2017
DOI: 10.1177/0037549717733051
|View full text |Cite
|
Sign up to set email alerts
|

Hypersonic flow past nose cones of different geometries: a comparative study

Abstract: The present work provides a detailed comparative study of the hypersonic flow past spherically blunted and parabolic nose cones at a Mach number of 5.8, numerically. The main focus of the paper is to determine the geometry and parameters of the nose cones that provide minimum aerodynamic drag and heating. Studies on spherically blunted and parabolic nose cones are performed for different fineness ratios at zero angle of attack. It is observed that for fineness ratio \1.2, blunted cones provide minimum drag, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Given that the rocket velocity will range up to Mach 3, the Von Karman geometry is selected as the candidate for optimization. [1][4][5] [6] 3 Design…”
Section: Comparison Studiesmentioning
confidence: 99%
“…Given that the rocket velocity will range up to Mach 3, the Von Karman geometry is selected as the candidate for optimization. [1][4][5] [6] 3 Design…”
Section: Comparison Studiesmentioning
confidence: 99%
“…But the research does not discuss the flow parameters of the bullet shapes. In the research works of Narayan [2].flow past over various nose geometry gives us a detailed view of flow over different nose geometry & gives a clear vision of the shock generated by the nose shapes. in the research thesis of Wilcox [3] Formulation of the k-w Turbulence Model, explains about the k-omega turbulence model uses an approximation for the Reynolds-averaged Navier-Stokes equations in computational fluid dynamics (RANS equations).…”
Section: IImentioning
confidence: 99%
“…The flow past different geometry forms of the nose has been completed, according to the study of Narayan [2]. The Mach number contours of a spherically blunted nose and a parabolic nose have been obtained as a result of the testing.…”
Section: A Flows Past Over Various Bullet Shapesmentioning
confidence: 99%
“…Previously, the effects of spike on flow structure around the nose and drag reduction were studied widely by both experimental and numerical approaches [2][3][4][5][6][7][8][9]. Stalder and Nielsen [1], who conducted measurements with spikes at high Mach number, indicated that aerodynamic drag of the model decreases with increasing length up to two times of diameter.…”
Section: Introductionmentioning
confidence: 99%